Correction: Research into the thermal stability and mechanical properties of vitamin E diffusion modified irradiation cross-linked graphene oxide/ultra-high molecular weight polyethylene composites. Issue 38 (11th June 2020) - Duan, Weipeng; Wu, Meiping; Han, Jitai
Abstract : Correction for 'Research into the thermal stability and mechanical properties of vitamin E diffusion modified irradiation cross-linked graphene oxide/ultra-high molecular weight polyethylene composites' by Weipeng Duan et al., RSC Adv., 2020, 10, 4175–4188, DOI: ; 10.1039/C9RA09893C .